A phase I dose-escalation study of eribulin and S-1 for metastatic breast cancer - Sakiyama, T (Br J Cancer, 2015)
BACKGROUND: We evaluated the safety, maximum-tolerated dose (MTD), pharmacokinetics, recommended dose for phase II (P2RD), and preliminary anticancer activity of a combination eribulin and S-1 therapeutic in metastatic breast cancer patients pretreated with anthracycline and taxane. METHOD: Patients aged 20–74 years were recruited. In level 1, patients received S-1 (65 mg m(−2)) from day 1 to 14, and eribulin (1.1 mg m(−2)) on day 1 and 8 in a 21-day cycle. In level 2, eribulin was increased to 1.4 mg m(−2). In level 3, S-1 was increased to 80 mg m(−2). RESULTS: Twelve patients were enrolled into three cohorts. Planned dose escalation was completed, with one case exhibiting dose-limiting toxicity (grade 3 hypokalaemia) at level 3, without reaching the MTD. The P2RD was determined to be level 2 (eribulin 1.4 mg m(−2) and S-1 65 mg m(−2)). The most common grade 3 or 4 toxicity was neutropenia (83.3%), followed by febrile neutropenia (25.0%). Five of eleven patients (41.7%) with measurable disease had a partial response. Pharmacokinetics were characterised by dose-dependent elimination and nonlinear exposure. CONCLUSION: Dose level 3 was not tolerated owing to febrile neutropenia development. Thus, intermediate dose level 2 was recommended for further evaluation. Preliminary antitumour activity warrants further investigation in this setting.